A Microelectrode Study of Hippocampal Electrical Activity in the Behaving Rat with Special Reference to Hypersynchronous Discharges - Suzuki, Shinya (My University, 1983)
The general purpose of this work is to examine the patterns of hippocampal EEG and unit activity during various behavioral states in the rat. Previous research indicates that the hippocampus generates rhythmical slow activity (RSA) during movement and paradoxical sleep. Other states are accompanied by irregular EEG containing "spikes" which are the main subject of this study.
Experiment 1 showed that most neurons in the dorsal hippocampus could be classified into four types according to their firing repertoires and behavioral correlates. Complex spike cells fired core frequently during non-RSA than during RSA. Theta cells, granule cells and fast complex spike cells showed the opposite pattern. Multiunit population bursts (PBs) were observed only during non-RSA. Experiment 2 indicated that in CA1 the PB was accompanied by an EEG spike (SPK) which was positive in oriens and negative in radiatum. SPKs occurred synchronously in the two hippocampi: Experiment 3 revealed that the laminar profile of evoked EPSPs was similar to that of SPKs. Both SPKs in radiatum and PBs in pyramidale were best mimicked by brief trains of high frequency pulses (20-60 msec, 125-250 Hz) applied to afferents. Experiment 4 showed that SPKs and their behavioral correlates were preserved after medial septal and/or entorhinal cortical lesions. Experiment 5 indicated, that SPKs and PBs were reduced by ether, urethane, pentobarbital and diazepam, while they were enhanced by bicuculline. They were not affected by atropine.
These results support the following conclusions. (1) Hippocampal pyramidal cells tend to fire synchronously in bursts during non-RSA states. (2) The CA1 SPK represents a synchronous excitation of middle apical dendrites triggered by synchronous bursts in CA3 via-the Schaffer collateral and commissural fibers. (3) These synchronous events occur when GABA-mediated inhibition is weak. (4) Activation of ascending inputs concurrent with RSA-related behaviors can suppress hippocampal SPKs via medial septal, entorhinal or other pathways.
Keywords: Psychology; Psychology